An investigation into the production of hydrogen and carbon nanomaterials by the thermocatalytic decomposition of methane - Wang, Hongyan (2013)
Hydrogen is widely considered to be one of the most promising alternative energy carriers and clean fuels. Hence, much effort has been directed in developing efficient, economic and environmental friendly approaches for the production of hydrogen. Among the many hydrogen production reactions, the catalytic decomposition of methane (CDM) over supported nickel catalysts has generated much interest. The major driving factor for the research activities on catalytic methane decomposition is the highly desirable products- COx-free hydrogen and carbon nanotubes (CNTs) or carbon nanofibres (CNFs) instead of gaseous COx. This reaction will eliminate the need for COx separation and sequestration processes altogether. The main objective of this research project is to produce hydrogen by thermal decomposition of methane over pure metallic catalysts and to optimize the process by developing high efficiency and long active-life catalysts. In this thesis, a comprehensive study on a series of unsupported nano-particle catalysts such as Ni, Ni-Cu and Ni-Cu-Co was presented. These unsupported catalysts prepared in a facile method showed comparable catalytic activity as the supported catalysts, and offered two major advantages by (1) providing easy recovery of the catalyst and a convenient way for the purification of the CNFs by leaching the metal catalyst with a mild acid solution and (2) preventing the formation of traceable CO which may be generated in supported (SiO2 and Al2O3) catalysts. To the best knowledge of the author, this study was the first time that investigated the catalytic activities and deactivation mechanisms of Ni, Ni-Cu and Ni-Cu-Co alloy particles towards CDM systematically. The thesis consisted mainly of the following five parts: (1) Unsupported NiO and NiO-CuO nano-particles were prepared by a facile method and these nano-particles showed promising catalytic activity towards CDM. Unlike the supported catalysts, it was necessary to introduce methane to the reactor at lower temperatures to avoid catalyst particles sintering into bigger ones during the reaction. The textural and micro-structural properties of the deposited carbon were also characterized in detail. This work provided helpful guidance on the direct preparation of active metallic catalysts in the next chapters. (2) Metallic nickel nano-particles were prepared primarily as catalysts for CDM. Nickel particle aggregates with controlled crystalline size and primary particle size were prepared firstly by the precipitation of nickel nitrate and oxalic acid in ethanol solution, followed by the thermal decomposition of nickel oxalate dihydrate under oxygen-free atmosphere. A series of decomposition atmospheres (CH4-N2 in different ratios) were used to investigate their effects on the morphology and crystalline size of the metallic nickel particles. The effects of ramp-up rate and reaction temperatures on the catalytic activity were also studied (3) A series of Ni-Cu alloy particles with different atomic ratios of Ni/Cu were prepared by the thermal decomposition of fibrous Ni-Cu oxalate precursors in methane atmosphere. The resulting porous aggregates of Ni-Cu alloy particles showed promising catalytic activities for methane decomposition at temperatures of 700 and 750°C. The stability of the catalysts was discussed and the deactivation mechanism was proposed. (4) A series of unsupported Ni-Cu-Co alloy particles with promising catalytic activity were prepared by thermal decomposition of Ni-Cu-Co oxalates in methane atmosphere. The addition of cobalt led to the formation of alloy particles with smaller crystalline size and particle size than those of Ni-Cu alloy or pure Ni particles. The objective of this part of the project was to investigate the genesis of the phase composition and properties of Ni-Cu-Co alloy catalyst. The effect of the addition of cobalt to the Ni-Cu catalyst on the stability of the catalyst was studied. (5) In this chapter, a detailed catalytic deactivation study was carried out. A series of kinetic experiments had been conducted using two types of catalysts (Ni and Ni-Cu-Co alloy). The effects of methane partial pressure and reaction temperatures on the maximal hydrogen formation rate were studied. The reaction order and activation energy of pure Ni and Ni-Cu-Co catalyst were calculated. Two models including the empirical model (General Power Law Equation) and a phenomenal model (Exponential Decay Model) were used to fit the experimental results of Ni catalysts. Different deactivation mechanisms of pure Ni and Ni-Cu-Co catalyst were proposed and discussed.